Illusions of democracy - Lemière, Sophie (Malaysian politics and people, 2017)
Bringing together a group of both international and Malaysian scholars, Illusions of Democracy: Malaysian Politics and People Volume II offers an up-to-date and broad analysis of the contemporary state of Malaysian politics and society. Transcending disciplinary boundaries, it offers a look at Malaysian politics not only through the lens of political science but also anthropology, cultural studies, international relations, political economy and legal studies touching on both overlooked topics in Malaysian political life as well as the emerging trends which will shape Malaysia's future. Covering silat martial arts, Malaysia's constitutional identity, emergency legislation, the South China Sea dilemma, ISIS discourse, zakat payment, the fallout from the 1MDB scandal and Malaysia's green movement, Illusions of Democracy charts the complex and multi-faceted nature of political life in a semi-authoritarian state, breaking down the illusions which keep it functioning, to uncover the mechanisms which really underlie the paradoxical longevity of Malaysia's political, economic and social system. 'Illusions of Democracy brings together over a dozen experts in Malaysian politics and society to explore various dimensions of identity, religion, regionalism, and power in contemporary Malaysia. At a time of political uncertainty in Malaysian politics, these contributions make for compelling reading for scholars and citizens alike.' Thomas Pepinsky Associate Professor of Government, Cornell University